Skaraborgs Sjukhus – Kartläggningar av lokaler och byggnader - Chalien, Adan (My University, 2014)
E2014:011 This bachelor thesis deals with healthcare. Which is a current and urgent subject. It concerns specifically Skaraborg´s Hospital, one out of four hospital groups within the Västragötaland´s Region. This hospital group in turn consists of the hospitals in Falköping, in Lidköping, in Mariestad and in Skövde. Skaraborg´s Hospital is after a recent reorganization of an extensive degree, divided into four different main areas (divisions) with a total of approximately 4 200 employees. The four main areas (divisions) are (1) Surgery (K), (2) Medicine and Psychiatry (M), (3) Research and Educational Development (FoUU), and (4) Stab including Human Relations (HR) and Economy. There are today some specific difficulties to in adequate ways monitor and understand the different activities within Skaraborg´s Hospital. Such relationships naturally creates obstacles for example to carry out organizational and occupational work. One such example is the lack of opportunity to link main areas (i.e. divisions), sub-‐divisions and organizational units with the surfaces and premises that these uses today. The aim of the bachelor thesis is (for these and other reasons) to connect the different organizational units, etc. within Skaraborg´s Hospital to the surfaces and premises that they use, and to thus make it possible to describe the main areas (divisions), sub-‐divisions and organizational units with more accurate and practical denotations, so that they can be understood by business representatives (patients) and employees. Due to the fact that Skaraborg´s Hospital is a large and complex organization, I have enclosed the thesis by primarily study only one medical subdivision, which is M.3 and consists of seventeen organizational units providing care by means of mainly three medical specialties, namely cardiology, skin infection and renal medicin. Subdivision of M.3 was chosen for this entire activity is located in the same locality, which is in Skövde. But also due to the fact that this was one of the more complex organizational units contributed to this choice. The bachelor thesis contains seven appendices, in which the thesis so-‐called method steps are detailed further, which also includes the appropriate sub-‐results. Thereby are the results comprised in these appendixes. Observe, that some of what are presented are contributions from other authors, i.e. results from a progressive research project within Skaraborg’s Hospital. These appendices are called (1) “Skaraborg´s Hospital a short description”, (2) “The work with the four Excel documents”, (3) “Buildings within Skövde hospital illustrated with current building drawings from Västfastigheter, in combination with a developed scheme to show such buildings”, (4) “Results from the physical inventories of the surfaces and premises within the subdivision M.3”, (5) “Suggestions for more accurate and practical denotations on areas (divisions), sub-‐ division and organisational units”, (6) “Example of a survey proposed to be sent to unit managers within the subdivision M.3 to ensure the results of the physical inventory” and (7) “Comments on some results obtained from a semi-‐structured interview with one of the managers (i.e. a doctor responsible for some of the activities whithin Research and Educational Development FoUU). The thesis is based on a number of Excel-‐documents obtained from Skaraborg´s Hospital and drawings of the premises obtained from Västfastigheter. It is also based on a variety of field trips where I have been able to visit and thereby carry out the physical inventories of the surfaces and premises of the selected organizational units and interviews of a number of key employees. The theoretical framework for this thesis is partly based on organization and organizational management, organizational culture and work of change within an organization and the working environment and safety responsibilities. The thesis is also based on theories and studies that have been done on healthcare organizations and healthcare management. The thesis work has helped to identify all surfaces and premises that organizational units within the subdivision M.3 exploits, and to provide suggestions for more accurate and functional denotations for these organizational units. This thesis also provides a better foundation for various ongoing and future initiatives to improve efficiencies as well as work and work conditions within Skaraborg´s Hospital. An example of the results thereby gained, is that the method used to identify both the surfaces and premises subdivision M.3 uses, which can be used for all of the other subdivisions and organizational units than those that have been studied in this thesis frames.
Keywords: Övrig industriell teknik och ekonomi; Grundläggande vetenskaper; Hållbar utveckling; Transport; Other industrial engineering and economics; Basic Sciences; Sustainable Development; Transport